Is Cost-Cutting Evidence of X-Inefficiency? - Borenstein, Severin; Farrell, Joseph (American Economic Review, 2000)
X-inefficiency is surely among the most important topics in microeconomics. Yet, economists have found it difficult to study. If a given level of X-inefficiency were inevitable and changeless, it would be of little interest (indeed, would not really deserve to be called X-inefficiency at all). So our attention should focus on actual and potential changes in X-inefficiency: that is, on causes of changes, internal to a firm, that shift the firm's cost function. We explore the use of firms ' “cost-cutting” announcements to study the causes of changes in X-inefficiency. Cost cutting announcements by large corporations are made frequently and are reported in the business press. One might be tempted to interpret these announcements as indicating efforts to reduce X-inefficiency, and indeed we